Evaluate the Effect of Some Chemicals (Phosphate, Nitrate and Silica) in Aquatic Systems of Epipelic Diatoms in Nisi Pond, Turkey - Erdal Sivaci, Ridvan (Asian Journal of Chemistry, 2013)
This work was described the relation between the epipelic diatom flora and physico-chemical of Nisi pond. Samples were collected monthly between December 2004 and June 2005 at random stations and PO4-P, PO4, P2O5, NO3-N, NO3, Si, SiO2, SO4,Cl, pH, O2, temperature (ºC), Cl-a and Caretoneit were measured in water. Physico-chemical data of Nisi pond shown that concentrations of P2O5, SiO2 and NO3-N were negatively correlated with temperature. PO4-P and PO2 concentration of water were observed positively correlation with the density of epipelic diatoms. A total 34 taxa belonging to 16 genera were identified. In the study period, Cymatopleura solea (Brébisson) W. Smith, Cymbella affinis Kützing, Epithemia adnata (Kützing) Brébisson, Nitzschia amphibia Grunow. were the most dominant species.